Finding Space for Traditional Medicine in the National Health Insurance Scheme in Ghana: Insights From Stakeholders - Maximillian Kolbe Domapielle (The International Journal of Health Planning and Management, 2026)
ABSTRACT This article analyses the practicability of integrating the products and services of traditional medicine practitioners into the benefits package of the National Health Insurance Scheme (NHIS) in Ghana. There appears to be a consensus among scholars that the integration of traditional medicine into health systems in low‐and middle‐income countries (LMICs) can improve access to primary healthcare for populations in underserved communities, yet the perspective of key actors on the practicality of including the services of traditional medicine practitioners in the benefits package of the NHIS has not been explored. A qualitative approach was deployed to collect and analyse the data. In specific terms, semi‐structured in‐depth interviews, and Focused Group Discussions (FGDs) were employed to explore stakeholders' views on the prospects and potential barriers of including traditional medicine into the operations of the NHIS. The study found that despite the general acceptance of the view that traditional medicine plays an important part in providing primary health care to health care clients, there is scepticism about the viability of including the products and services of Traditional Medicine Practitioners (TMPs) in the benefits package of the NHIS. They argue that in spite of the existence of regulatory frameworks and guidelines for the use of traditional herbal products in modern health facilities, the criteria for including the products and services of traditional medicine practitioners in the benefits package of the NHIS are restrictive and are likely to exclude the majority of TMPs from participating in the NHIS. The study advocates further research to inform the development and implementation of an inclusive regulatory framework for an integrated healthcare system in the country.